2008
DOI: 10.1128/jcm.02051-07
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Analysis of Initial Colonization of Periodontal Pathogens in Oral Cavity

Abstract: It is unclear when the initial colonization by periodontal pathogens occurs in the oral cavity. Therefore, we report here the association between specific age groups and the time when the initial colonization by periodontal pathogens occurs in the oral cavity in such groups. Findings are based on an epidemiological analysis of the prevalence of five periodontal pathogens in the oral cavities of a wide range of age populations, from newborn to elderly, who were randomly selected in a geographic region of Brazil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 36 publications
2
67
3
1
Order By: Relevance
“…48,49 Among these unclean surfaces many are colonized by bacteria since early childhood. 50 However, in the present survey only 27.3% of professionals stated that the cleaning of sites other than teeth and tongue was a reason to prescribe mouthrinses, which is inconsistent with scientific data. Therefore, additional efforts should be made to generalize this specific knowledge among dentists.…”
Section: Reasons For Mouthrinse Usecontrasting
confidence: 82%
“…48,49 Among these unclean surfaces many are colonized by bacteria since early childhood. 50 However, in the present survey only 27.3% of professionals stated that the cleaning of sites other than teeth and tongue was a reason to prescribe mouthrinses, which is inconsistent with scientific data. Therefore, additional efforts should be made to generalize this specific knowledge among dentists.…”
Section: Reasons For Mouthrinse Usecontrasting
confidence: 82%
“…According to Kamma et al [21], 22-to 35-year-old smoking patients with early onset periodontitis harbored greater numbers of bacteria, mainly anaerobes such as P. gingivalis and T. forsythia. However, Cortelli et al [43] found no correlation between smoking and the prevalence of A. actinomycetemcomitans, P. gingivalis, T. forsythia, or P. intermedia. In our study, the duration and quantity of smoking as assessed using the pack-year data intensified the effect of smoking on the frequency of the positive bacterial samples in the girls.…”
Section: Discussionmentioning
confidence: 95%
“…Pooled subgingival samples were taken from five periodontal sites (> PD) 20 . Each selected tooth was isolated with sterile cotton rolls and the supragingival plaque was removed with sterile cotton pellets.…”
Section: Microbiological Examinationmentioning
confidence: 99%